Avian Paramyxovirus Type-3 as a Vaccine Vector: Identification of a Genome Location for High Level Expression of a Foreign Gene - Yoshida, Asuka; Samal, Siba K. (Frontiers in Microbiology, 2017)
Avian paramyxovirus serotype 3 (APMV-3) causes infection in a wide variety of avian species, but it does not cause apparent diseases in chickens. On the contrary, APMV-1, also known as Newcastle disease virus (NDV), can cause severe disease in chickens. Currently, natural low virulence strains of NDV are used as live-attenuated vaccines throughout the world. NDV is also being evaluated as a vaccine vector against poultry pathogens. However, due to routine vaccination programs, chickens often possess pre-existing antibodies against NDV, which may cause the chickens to be less sensitive to recombinant NDV vaccines expressing antigens of other avian pathogens. Therefore, it may be possible for an APMV-3 vector vaccine to circumvent this issue. In this study, we determined the optimal insertion site in the genome of APMV-3 for high level expression of a foreign gene. We generated recombinant APMV-3 viruses expressing the green fluorescent protein (GFP) by inserting the GFP gene at five different intergenic regions in the genome. The levels of GFP transcription and translation were evaluated. Interestingly, the levels of GFP transcription and translation did not follow the 3’-to-5’ attenuation mechanism of non-segmented, negative-sense RNA viruses. The insertion of GFP gene into the P-M gene junction resulted in higher level of expression of GFP than when the gene was inserted into the upstream N-P gene junction. Unlike NDV, insertion of GFP did not attenuate the growth efficiency of AMPV-3. Thus, APMV-3 could be a more useful vaccine vector for avian pathogens than NDV.